The Role of Platelets in the Stimulation of Neuronal Synaptic Plasticity, Electric Activity, and Oxidative Phosphorylation: Possibilities for New Therapy of Neurodegenerative Diseases - Kopeikina, Ekaterina; Ponomarev, Eugene D. (Frontiers in Cellular Neuroscience, 2021)
The central nervous system (CNS) is highly vascularized where neuronal cells are located in proximity to endothelial cells, astroglial limitans, and neuronal processes, thus constituting integrated neurovascular units. In contrast to many other organs, the CNS has a blood-brain barrier (BBB), which becomes compromised due to infection, neuroinflammation, neurodegeneration, traumatic brain injury, and other reasons. Experimental evidence demonstrated that BBB permeability substantially increases during many types of neurodegenerative disorders. Moreover, BBB disruption is presumably involved in neuronal injury during epilepsy and psychiatric disorders. Therefore, many types of neuropsychological disorders are accompanied by an increase in BBB permeability leading to direct contact of circulating blood cells in the capillaries with neuronal cells in the CNS. The second most abundant type of blood cells are platelets, which come after erythrocytes and outnumber ~100-fold circulating leukocytes. When BBB becomes compromised, platelets swiftly respond to the vascular injury and become engaged in thrombosis and hemostasis. However, more recent studies demonstrated that platelets could also enter CNS parenchyma and directly interact with neuronal cells. Within CNS, platelets become activated by recognizing major brain gangliosides on the surface of astrocytes and neurons and releasing a milieu of pro-inflammatory mediators, neurotrophic factors, and neurotransmitters. Platelet-derived factors directly stimulate neuronal electric and synaptic activity and promote the formation of new synapses and axonal regrowth near the site of damage. Despite such active involvement in response to CNS damage, the role of platelets in neurological disorders was not extensively studied, which will be the focus of this review.